Project portfolio management: an analysis from the insurance industry IT area - Pitorri, Fabio (2014)
This paper aims to bring more information related to the critical question 'how IT areas of insurance companies are defining and delivering their strategic initiatives Portfolios?' and make conclusions based on the collected data. To reach these interpretations, it is composed of a theoretical investigation on the theme, a strategy delineation for the research methodology and a conclusion presentation based on the findings. In this last part, this study concluded that explored organization does not applied a sufficient number of best practices answering the critical question as 'the company is not mature on this subject'.